Market characteristics and awareness of managed care options among elderly beneficiaries enrolled in traditional medicare. - Mittler, Jessica N; Landon, Bruce E; Zaslavsky, Alan M; Cleary, Paul D (Medicare & medicaid research review, 2011)
Medicare beneficiaries' awareness of Medicare managed care plans is critical for realizing the potential benefits of coverage choices.